Shenmai Injection Protects Against Doxorubicin-Induced Cardiotoxicity via Maintaining Mitochondrial Homeostasis - Li, Lin; Li, Jinghao; Wang, Qilong; Zhao, Xin; Yang, Dongli; Niu, Lu; Yang, Yanze; Zheng, Xianxian; Hu, Limin; Li, Yuhong (Frontiers in Pharmacology, 2020)
Shenmai injection (SMI), as a patented traditional Chinese medicine, is extracted from Panax ginseng and Ophiopogon japonicus. It commonly used in the treatment of cardiovascular disease and in the control of cardiac toxicity induced by doxorubicin (DOX) treatment. However, its anti-cardiotoxicity mechanism remains unknown. The purpose of this study was to investigate the underlying mitochondrial protective mechanisms of SMI on DOX-induced myocardial injury. The cardioprotective effect of SMI against DOX-induced myocardial damage was evaluated in C57BL/6 mice and H9c2 cardiomyocytes. In vivo, myocardial injury, apoptosis and phosphoinositide 3-kinase (PI3K)/protein kinase B (PKB/Akt)/glycogen synthase kinase 3 beta (GSK-3β) signaling pathway related proteins were measured. In vitro, apoptosis, mitochondrial superoxide, mitochondrial membrane potential, mitochondrial morphology, levels of mitochondrial fission/fusion associated proteins, mitochondrial respiratory function, and AMP-activated protein kinase (AMPK) activity were assessed. To further elucidate the regulating effects of SMI on AMPK and PI3K/Akt/GSK-3β signaling pathway, compound C and LY294002 were utilized. In vivo, SMI decreased mortality rate, levels of creatine kinase, and creatine kinase-MB. SMI significantly prevented DOX-induced cardiac dysfunction and apoptosis, decreased levels of Bax/Bcl-2 and cleaved-Caspase3, increased levels of PI3K, p-Akt, and p-GSK-3β. In vitro, SMI rescued DOX-injured H9c2 cardiomyocytes from apoptosis, excessive mitochondrial reactive oxygen species production and descending mitochondrial membrane potential, which were markedly suppressed by LY294002. SMI increased ratio of L-OPA1 to S-OPA1, levels of AMPK phosphorylation, and DRP1 phosphorylation (Ser637) in order to prevent DOX-induced excessive mitochondrial fission and insufficient mitochondrial fusion. In conclusion, SMI prevents DOX-induced cardiotoxicity, inhibits mitochondrial oxidative stress and mitochondrial fragmentation through activation of AMPK and PI3K/Akt/GSK-3β signaling pathway.